Cinnamic Acid Derivatives and their Biological Efficacy - Ngonidzashe Ruwizhi (International Journal of Molecular Sciences, 2020)
The role played by cinnamic acid derivatives in treating cancer, bacterial infections, diabetes and neurological disorders, among many, has been reported. Cinnamic acid is obtained from cinnamon bark. Its structure is composed of a benzene ring, an alkene double bond and an acrylic acid functional group making it possible to modify the aforementioned functionalities with a variety of compounds resulting in bioactive agents with enhanced efficacy. The nature of the substituents incorporated into cinnamic acid has been found to play a huge role in either enhancing or decreasing the biological efficacy of the synthesized cinnamic acid derivatives. Some of the derivatives have been reported to be more effective when compared to the standard drugs used to treat chronic or infectious diseases in vitro, thus making them very promising therapeutic agents. Compound 20 displayed potent anti-TB activity, compound 27 exhibited significant antibacterial activity on S. aureus strain of bacteria and compounds with potent antimalarial activity are 35a, 35g, 35i, 36i, and 36b. Furthermore, compounds 43d, 44o, 55g–55p, 59e, 59g displayed potent anticancer activity and compounds 86f–h were active against both hAChE and hBuChE. This review will expound on the recent advances on cinnamic acid derivatives and their biological efficacy.